Race and socioeconomic effect on sarcopenia and sarcopenic obesity in the Louisiana Osteoporosis Study (LOS). Issue 2 (1st July 2018) - Jeng, Cassie; Zhao, Lan‐Juan; Wu, Kehao; Zhou, Yu; Chen, Ted; Deng, Hong‐Wen
Abstract: Background: Sarcopenia and sarcopenic obesity are emerging public health issues. True prevalence rates are unknown and estimates differ substantially between studies. No large‐scale single study has compared prevalence rates between whites, blacks, Asians, and Hispanics, as we intend to do here. This study also examined the effects of race and socioeconomic factors on sarcopenia and sarcopenic obesity. Methods: This study included 10, 325 participants from Louisiana. Appendicular lean mass (ASM), measured through dual energy x‐ray absorptiometry (DXA) scans, was divided by height squared (ASM/h 2 ) to define sarcopenia. Sarcopenic obesity was defined as sarcopenia plus obesity (waist‐to‐hip ratio). Results: Overall sarcopenia and sarcopenic obesity rates were 17.6% and 7.0% for males, and 13.7% and 2.5% for females, respectively. The highest sarcopenia and sarcopenic obesity rates were found in Asian males (40.6%, 14.4%) and females (30.1%, 8.0%). The lowest sarcopenic obesity rates were observed in black males (3.7%) and females (0.9%). We found significant associations with sarcopenic obesity in males for age, race, and income; in females, for age, race, and education. Conclusions: Under one diagnostic definition, the prevalence of sarcopenia and sarcopenic obesity is highest among Asians and lowest amongst blacks. Income and education had significant associations with sarcopenia and sarcopenic obesity, in males and females, respectively.